A Project Report on Automated E-Mail Reading System - JAGADISHWAR K, SNADEEP JAJEE, SHARANAPPA and SOMNATH M (2006)
INTERNAL GUIDE: RAMARAJAN, MVJCE EXTERNAL GUIDE: T ESSAKI MUTTHU, MVJCE
Keywords: E-Mail Reading System